Waktu yang dihabiskan oleh kepala puskesmas keluar kantor untuk kegiatan administrasi versus program lapangan: analisis data fasilitas komunitas dari IFLS East 2012 - Veronika Suka; Ahmad Watsiq Maula; Dian Mawarni; Retna Siwi Padmawati; Mubasysyir Hasanbasri (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Health center manager time spending for outside administrative versus field work in East Indonesian region: an analysis of community facility of 2012 IFLS East PurposeThis study evaluates time spent on administrative and field public health program of physician or non-physician community health center managers in East Indonesian region. MethodThe study used 85 community health center managers from 7 provinces of East Nusa Tenggara, East Kalimantan, Southeast Sulawesi, Maluku, North Maluku, West Papua, and Papua from which the data was available in the community facility section of Indonesian Family Life Survey East (IFLS East) 2012.ResultsPhysician managers spent more hours than non-physician managers for administrative matters. In addition, non-physician managers had more hours per week for field program activities as compared to physician managers.ConclusionResearch shows that physician managers have potential lost of their time in performing their medical service functions, which they are trained for. Policy should be directed to improve the management skills of non physician health workers so that physicians can maximize their time to solve medical problems in health centers.